Pengembangan Media Pembelajaran dengan Bantuan Aplikasi Mtestm Kemampuan Mendengar A1 (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to create learning media with the help of MtestM application about German language students' knowledge of listening skill A1 topic